Physiological Responses of Soybean Varieties to Different Types of Biochar Application - Muji Rahayu; Andriyana Setyawati; Gani Cahyo Handoyo; Bramesty Laras Hanif; Fevi Catur Wulan Sari (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2025)
Soybeans, a legume widely consumed in Indonesia, exhibit a comparatively low production rate. Therefore, initiatives to augment soybean production are essential, one of which is the utilization of biochar. Biochar has been extensively studied as a soil amendment that improves soil fertility and promotes plant growth. This study aimed to evaluate the physiological responses of soybean varieties to different types of biochar. The experiment used a factor randomized complete block design (RCBD) with three replications. The factor was three soybean varieties (Dena 1, Demas 1, and Gepak Kuning) and three biochar treatments (control, palm fibre, and rice hull). Data were analysed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. Results indicated that rice hull biochar improved net assimilation and relative growth rates by 1.95% and 1.59%, respectively, between the third and fifth weeks after planting. It also increased total dry weight by 1.37% and leaf area index by 1.72% compared to untreated plants. Among the varieties tested, Dena 1 yielded the highest total dry weight (1.41%) and leaf area index (1.53%), highlighting a promising synergy between this variety and rice hull biochar. These findings demonstrate that biochar type and soybean variety interact to determine physiological responses, suggesting that appropriate combinations may improve soybean productivity and resilience under field conditions.